Đóng góp của ngành ICT vào tăng trưởng kinh tế Việt Nam giai đoạn 2000–2019 - Đặng Thị Việt, Đức; Đặng Huyền, Linh (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2021)
The objective of this paper is to clarify the contribution of the Information Communication Technology (ICT) sector to Vietnam's economic growth over the period of 2000–2019 by using a growth accounting model. The research results show that: First, Vietnam's ICT sector has a higher growth rate than the economy; Second, the contribution of Vietnam ICT’s TFP (total factor productivity) to the sector’s GDP growth is higher than that of the economy; and Third, the total contribution of the ICT sector's labor and capital inputs to Vietnam's economic growth is only 2.28%. In other words, although the ICT sector exhibits higher overall productivity than the economy average, the direct contribution to the economic growth of the ICT industry remains modest in Vietnam.
Keywords: ICT; Economic growth; Vietnam